Extending the existing geo-dbms to third dimension: the 3D data type and spatial operations - Abdul Rahman, Alias (2008)
Next generation of geo-DBMS would be given attention on extending its dimensionality and functionality in order to fill the demand in 3D applications, e.g. geosciences, subsurface, AEC, and etc. Current 3D GIS offer predominantly 2D functionality with 3D visualization and navigation capability. However, promising developments were observed in the DBMS domain where more spatial data types, functions and indexing mechanism were supported. In this aspect, DBMS are expected to become a critical component in developing of an operational 3D GIS. However, extended research and developments are needed to achieve native 3D support at DBMS level. One of the desired components in such future software or system is the geometric modeling that works with 3D spatial operations. The fundamental aspects of the 3D spatial operations are still not much been addressed up to the level where an operational 3D system could be realized. The main problem from this aspect is the unavailability of 3D spatial data type within geo-DBMS environment. It is the aim of this paper to describe 3D spatial operations for geometrical and topological models within geo-DBMS environment. In the experiment, we utilize an existing geo-DBMS, PostgreSQL, later known as PostGIS, that compliant to the standard specifications from Open Geospatial Consortium (OGC), e.g. abstract and geometry specification. The main reason about utilizing the PostGIS is because it is an open source based technology and suitable for educational purposes. In this paper, we discuss a suitable way of developing a new 3D data type, polyhedron, using C language. This polyhedron is a 3D equivalent of a set of polygon that bounds a solid object, in which by connecting them in a proper manner and sharing a common edge between two adjacent polygons. These new data types will be used as inputs for 3D spatial operations. The research focuses two types of 3D spatial operations, i.e. computational-geometry, and metric operations. The computational-geometry operations manipulate the coordinate triplet using the geometrical modeling approach, e.g. 3D intersection, 3D difference, 3D XOR, and 3D union. The metric operation deals with the mathematical computation, e.g. volume calculation of a polyhedron. The approach works and we highlighted the results by using the simple data sets. The research shows that the essential research findings are applicable for real world objects and provides a solution towards a full 3D analytical operation in future.